2016
DOI: 10.4236/jcdsa.2016.63014
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Cutaneous Leishmaniasis by Oral Zinc Sulfate and Oral Ketocanazole Singly and in Combination

Abstract: Background: Cutaneous Leishmaniasis (CL) is an endemic disease in many countries and caused by different species of Leishmania parasite. It results in a deformed scar after a relatively long period. Many therapies have been tried in treatment of this disease. Objective: To compare the effect of oral zinc sulfate and oral ketoconazole singly and in combination in the treatment of acute cutaneous leishmaniasis. Patients and Methods: This single, blinded, therapeutic, controlled study was conducted in the Departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…The time span of lesion improvement from the onset of treatment was 1.5 to 4.8 months, with the mean of 2.8±0.3. This result is not consistent with the literature and published data from other parts of Iraq that indicated CL improves in response to standard treatment within 6 weeks (11). Another group of authors from Iraq demonstrated that after the initiation of antileishmania treatment, CL lesion heals within 4 weeks in the majority of patients (12).…”
Section: Discussioncontrasting
confidence: 99%
“…The time span of lesion improvement from the onset of treatment was 1.5 to 4.8 months, with the mean of 2.8±0.3. This result is not consistent with the literature and published data from other parts of Iraq that indicated CL improves in response to standard treatment within 6 weeks (11). Another group of authors from Iraq demonstrated that after the initiation of antileishmania treatment, CL lesion heals within 4 weeks in the majority of patients (12).…”
Section: Discussioncontrasting
confidence: 99%
“…This diversity of cure rate could be explained by the higher dose of ketoconazole and the different scoring system and no side effects were reported. While Sharquie et al (15) used ketoconazole as a single therapy for leishmaniasis and gave 50% cure rate, and in a combination of oral ketoconazole and zinc sulfate gave a cure rate of 96%, and by using Tuckey HSD test suggests that this combination has synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous Leishmaniasis (CL) is an endemic disease in many countries including Iraq and many drugs were used in treatment of CL and KC is one of them. In Sharquieetal study, we used KC singly and in combination with oral zinc sulphate, and the results were very encouraging [15].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have treat various medical problems via the use of oral zinc sulfate (including viral warts (46), herpes simples infections (47), and acute cutaneous leishmaniasis) (48)(49)(50). Zinc sulfate is also used as a therapy for autoimmune diseases like alopecia areata (51), Behcet's disease (52), and recurrent aphthous stomatitis (53).…”
Section: Zinc Infection and Immunitymentioning
confidence: 99%